33 Value of pericardial fenestration in the diagnosis and treatment of tuberculous pericarditis. (6th June 2022) - Meng, Zi; Meng, Jia; Li, Xiao
Abstract : Objective: To explore the value of thoracoscopic pericardial fenestration in the diagnosis and treatment of tuberculous pericardial effusion. Methods: 55 patients with unexplained massive pericardial effusion underwent thoracoscopic pericardial fenestration. Results: 14 cases were diagnosed as tuberculous pericarditis by pericardial biopsy. There were no complications during and after operation. The thoracic drainage tube was pulled out 24 ~ 85 hours after operation (average 33.5 hours). During the follow-up, there was no recurrence of pericardial effusion and no constrictive pericarditis. Conclusion: Thoracoscopic pericardial fenestration is a safe and effective method, which can be used as a diagnosis and treatment method for a large number of pericardial effusion of unknown cause. Conflict of Interest: NO